2021
DOI: 10.3390/jof7010057
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Lactobacillus helveticus LA401 and Lactobacillus gasseri LA806 Combination Attenuates Oesophageal and Gastrointestinal Candidiasis and Consequent Gut Inflammation in Mice

Abstract: Candida albicans is an opportunistic pathogen that causes mucosal gastrointestinal (GI) candidiasis tightly associated with gut inflammatory status. The emergence of drug resistance, the side effects of currently available antifungals and the high frequency of recurrent candidiasis indicate that new and improved therapeutics are needed. Probiotics have been suggested as a useful alternative for the management of candidiasis. We demonstrated that oral administration of Lactobacillus gasseri LA806 alone or combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…In vivo studies in animal models –particularly in mice- show that lactobacilli can reduce Candida burdens and reverse dysbiosis. Candida -induced stomach lesions, gastric inflammation, and dysbiosis in murine models are attenuated by several species, i.e., L. rhamnosus [ 126 ], L. gasseri, L. helveticus [ 127 ], and L. pentosus [ 128 ], among others. Lactobacilli may also act as prophylactic agents.…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies in animal models –particularly in mice- show that lactobacilli can reduce Candida burdens and reverse dysbiosis. Candida -induced stomach lesions, gastric inflammation, and dysbiosis in murine models are attenuated by several species, i.e., L. rhamnosus [ 126 ], L. gasseri, L. helveticus [ 127 ], and L. pentosus [ 128 ], among others. Lactobacilli may also act as prophylactic agents.…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…Authier et al showed that combined oral administration of L. helveticus and L. gasseri reduced TNF-α, IL-1β, IL-8, and CRP inflammatory markers while increasing the expression of IL-1ra and IL-10 anti-inflammatory markers in colonic tissues of C. albicans -infected mice. Moreover, mRNA expression of enzymes involved in the synthesis of pro-inflammatory eicosanoids was also decreased [ 127 ]. Clinical trials also confirm the immunomodulatory properties of lactobacilli in humans.…”
Section: Anticandidal Properties Of Lactobacillimentioning
confidence: 99%
“…might have a neuroprotective action during the acute and chronic phases in a mouse model of TBI. Our selection was supported by literature documenting the beneficial effects of the Lactobacillus strains in various animal model studies, where modulation of the inflammatory response was a fundamental aspect of the disease process [60][61][62][63]. Different strains of Lactobacillus have been shown to decrease the production of inflammatory cytokines such as TNF-α and IL-6 [64,65], downregulate pro-apoptotic neurons, and activate inflammatory mediators [66].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, animal model experiments and clinical studies provide important data regarding the efficacies of probiotics. Several animal models of oral, gastrointestinal and vaginal candidiasis have been proposed for analyses of fungal immunity and anti-fungal therapies [11,17,18,[21][22][23][24][25][26][27]. These animal models have aided in elucidating molecular mechanisms related to candidiasis; they have also facilitated the evaluation of novel therapeutic approaches.…”
Section: Discussionmentioning
confidence: 99%